FORMATION AND ASSESSMENT OF “4K” COMPETENCE IN THE EDUCATIONAL PROCESS - Azimov, Yusufjon (Science technology&Digital finance, 2023)
The article discusses various aspects of the formation of “4K” competence in the creative pedagogical process in physics lessons